Plasma hsa_circ_0027089 is a diagnostic biomarker for hepatitis B virus-related hepatocellular carcinoma - Zhu, Kai (Carcinogenesis, 2020)
Circular RNAs (circRNAs) have recently been identified as a new member of endogenous noncoding RNAs. CircRNAs exhibit high stability and can thus can be used as valuable biomarkers for monitoring the occurrence and development of hepatocellular carcinoma (HCC). The present study sought to explore the diagnostic significance of plasma circRNAs in hepatitis B virus (HBV)-related HCC. Plasma circRNAs from 10 patients with hepatitis B (HBV)-related HCC and 5 patients with HBV-related liver cirrhosis were investigated by microarray to screen differentially expressed circRNAs, 157 upregulated and 161 downregulated circRNAs were found. Twenty-four circRNAs were further investigated via quantitative reverse-transcriptase–polymerase chain reaction assay in a training cohort (n = 48), hsa_circ_0027089 exhibited the highest significance and further distinguished 64 HCC patients from 40 cirrhosis patients and 72 healthy participants in a validation cohort. These results indicate that plasma hsa_circ_0027089 can serve as a new marker for the diagnosis of HBV-related HCC.